Hydroponics Virtual Laboratory as An Innovation in Online Learning Media During a Pandemic - Swestyani, Sondra; Ramadhani, Ayu Novita (Bioedukasi: Jurnal Pendidikan Biologi, 2022)
The Covid-19 pandemic has limited the role of laboratories in learning. Innovation in learning needs to be done, one of which is by using a virtual laboratory as a learning medium. This descriptive mix-method research aims to describe students’ activeness in online learning and the practicality of virtual laboratory learning media developed as learning media. This research was a dissemination stage of the 4-D development research. The instrument was observation sheets on the students’ activeness in online learning when using the hydroponic virtual laboratory. The results concluded that students’ activeness increased by an average of 22.2% after using a hydroponic virtual laboratory. The virtual laboratory was practical as shown by 73.9% of respondents agreeing and 22.9% of them strongly agree.